Design and validation of an educational questionnaire for evaluation of teachers by students in Shahid Beheshti dental school - Hadi Ghasemi; Arezoo Ebnahmadi; Maryam Moezzyzadeh; Masoud Geramipour (Tehran University of Medical Sciences, 2016)
Background and Aims: Dental students’ evaluation of teachers’ educational activity is crucial for the improvement of dental school’s performance. The process of the evaluation needs a valid and reliable tool. This study aimed to produce and validate a questionnaire for the evaluation of dental school teachers by students. Materials and Methods: A group of 15 teachers in the Shahid Beheshti dental school gave their opinions regarding the characteristics of an ideal teacher using nominal group technique. These characteristics together with characteristics gathered from similar studies made the base of a questionnaire which later underwent a validity and reliability assessment by means of the calculation of Content Validity Index (CVI), Content Validity Ratio (CVR), and Cronbach’s alpha coefficient. Results: The preliminary questionnaire included 94 items in four categories naming: ethics, educational capability, practical capability, and managemet. After calculating CVR and CVI for each item, 23 items with CVR<0.33 and 20 items with CVI<0.79 have been excluded from the questionnaire leaving a questionnaire with 54 items. The overall reliability of this questionnaire using Chronbach’s alpha coefficient was 0.96. Conclusion: Consulting an expert group that are familiar with different aspects of educational performance of faculty teachers, it was concluded that applying various methods for validity and reliability, and considering local culture values are useful for the preparation of the questionnaire for similar studies in Iran.